Composite powder filler as well as preparation method and application thereof

By using composite powder filler composed of porous silica and dense silica in the copper depositing process of printed circuit boards, the problem of hole wall cavity is solved, the reliability and conductivity of the circuit are improved, and the demand for high-performance printed circuit boards of electronic products is met.

CN119875202APending Publication Date: 2025-04-25ZHEJIANG THIRD AGE MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510132718.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-06
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The prior art often presents hole wall problems in the copper depositing process of printed circuit boards, resulting in a degradation of circuit reliability and conductivity.

Method used

Using a composite powder filler composed of porous silica and dense silica, the weight ratio of porous silica (0.5%~30%) and specific surface area (1.5~15m2/g) and particle size (0.3~2μm) of dense silica are used to improve the affinity of the substrate material with the electroplating copper solution, and the siphon effect is used to promote the filling of the copper solution.

Benefits of technology

It effectively avoids the formation of hole wall cavity, improves the bonding performance between the copper layer and the substrate film surface, enhances the peel strength of the copper layer, and meets the development needs of electronic products for miniaturization, lightweight, high-speed, high-frequency and multifunctional printing circuit boards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of semiconductor packaging, and discloses a composite powder filler and a preparation method and application thereof. The compact silicon dioxide is used as a main filler, and the porous silicon dioxide with the weight ratio of 0.5%-30% is added into the filler, so that on the premise of ensuring the filling rate of the filler, the affinity between a substrate material and an electroplating copper liquid can be improved, the electroplating copper liquid can be easily combined with a film surface in a copper deposition process, the problem of hole wall cavities is avoided, and meanwhile, the service life of the substrate is prolonged. The copper layer of the prepared PCB is tightly combined with the film surface of the substrate, and the prepared PCB has excellent peel strength. Besides, in the composite filler disclosed by the invention, the compact silicon dioxide is used as the main filler, so that the prepared substrate material has relatively high filling rate and good mechanical property, and can be suitable for being used in a scene with relatively high stress or pressure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of semiconductor packaging technology, and in particular to a composite powder filler and a preparation method and application thereof. Background Art

[0002] Printed Circuit Board (PCB) is a board that forms electrical connections between electronic components by laying conductive copper foil patterned on the surface of insulating material. The main function of PCB is to achieve electrical connections between electronic components through copper foil lines and to support components fixed on the board. Currently, PCBs include HDI (High Density Interconnection) boards, IC packaging substrates, rigid-flex boards, embedded component boards, optoelectronic boards, special substrate printed boards, etc. The development trend of electronic products requires printed circuit boards to develop in the direction of miniaturization, lightweight, high speed, high frequency and multi-function.

[0003] The general process flow of PCB circuit boards includes: cutting, drilling, copper plating, pattern transfer, pattern electroplating, etching, solder mask, characters, surface treatment, appearance reaming, final inspection, packaging and shipment. Hole wall voids refer to tiny gaps that are not filled with copper inside the through holes or at the connections between layers of PCB circuit boards. These voids will reduce the reliability and conductivity of the circuit, and in severe cases may even cause the circuit board to be scrapped. Drilling is to create precise holes on the PCB board to achieve electrical connections between different layers or to install electronic components; copper plating is the abbreviation of electroless plating copper. The problem of forming hole wall voids is one of the common problems in the copper plating process of PCB circuit boards.

[0004] At present, the main measure to avoid the formation of hole wall voids is to decontaminate the holes on the multi-layer PCB board and increase the roughness of the drilling film surface before the copper deposition process to improve the affinity between the copper layer and the film surface, thereby avoiding the formation of hole wall voids. The decontamination treatment is mainly divided into two types: wet and dry. The wet treatment includes concentrated sulfuric acid, concentrated chromic acid, potassium permanganate and PI (polyimide) adjustment treatment to remove glue residue or other stains.

[0005] In the prior art, another major measure to avoid the formation of hole wall voids is to achieve the filling performance of the copper plating liquid by adding additives such as accelerators, inhibitors, and levelers, so that the copper layer structure becomes more delicate and easy to combine with the drilled film surface, thereby avoiding the formation of hole wall voids. For example, a Chinese patent with application publication number CN113430597A discloses an application of a circuit board hole filling electroplating leveler, which improves the hole filling performance of the plating solution during hole filling electroplating through the innovation of the leveler. However, the hole filling effect of this method fails to meet the high requirements of the current refinement of electronic products, and the phenomenon of hole wall voids still occurs. Summary of the invention

[0006] In order to avoid the problem of hole wall voids during copper electroplating, the present invention provides a composite powder filler and a preparation method and application thereof.

[0007] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a composite powder filler consisting of porous silica and dense silica, wherein the weight of the porous silica accounts for 0.5% to 30% of the total weight of the filler.

[0008] The problem of pore wall voids occurs when copper is deposited on a PCB circuit board, mainly due to poor interface compatibility between the substrate surface and the copper electroplating solution. The present invention uses porous silica and dense silica in a suitable ratio as composite fillers to make a substrate, and copper deposition on this substrate can effectively avoid the pore wall void phenomenon, wherein the suitable ratio is that the weight of the porous silica accounts for 0.5% to 30% of the total weight of the filler.

[0009] Using dense silica as filler can make the prepared substrate material have a good filling rate, good mechanical properties, and can be used in scenes with high stress or pressure, but too much dense silica will cause the bonding ability between the substrate material and the copper foil layer to deteriorate sharply, thus easily leading to the problem of hole wall voids during copper deposition. The present invention uses dense silica as the main filler and adds porous silica at a weight ratio of 0.5% to 30%, which can improve the affinity between the substrate material and the electroplating copper solution while ensuring the filling rate of the filler, facilitate the combination of the electroplating copper solution with the membrane surface, avoid the formation of the hole wall void problem, and the copper layer of the prepared PCB circuit board is tightly combined with the substrate membrane surface.

[0010] The porous silica with a weight ratio of 0.5% to 30% can absorb the electroplating copper liquid into the pores of the silica due to its pores during the copper deposition process with the help of the physical siphon effect, so that the copper liquid can be guided to quickly fill the drilled holes of the substrate during copper deposition, thereby improving the bonding performance between the copper layer of the finished PCB circuit board and the membrane surface of the substrate. Due to the existence of the siphon effect, the formation of voids in the hole wall is avoided.

[0011] In the above method of the present invention, the dense silica can be understood as non-porous silica. Generally, dense silica is a silica material with a relatively high density and a relatively compact structure, and its surface is dense and has no pores or fewer pores. The dense silica can be prepared by chemical synthesis, deflagration, flame melting, etc.

[0012] As the composite powder filler, preferably, the average pore size of the porous silica is 5 to 100 nm based on the BJH method.

[0013] When the average number of the pore size of porous silica is 5-100nm, the formation of pore wall voids can be effectively avoided. If the pore size of porous silica is too small, the electroplating copper solution cannot enter the pores, which will cause the copper layer of the product PCB circuit board to have poor bonding performance with the substrate film surface. The present invention has been found through multiple tests that if the pore size of porous silica is too large, the electroplating copper solution cannot completely fill the pores, and at this time, the bonding performance of the copper layer of the product PCB circuit board with the substrate film surface is poor.

[0014] As the composite powder filler, preferably, the average pore size of the porous silica is 10 to 50 nm based on the BJH method.

[0015] When the average pore size of porous silica is 10~50nm, the formation of pore wall voids can be more effectively avoided. Within this pore size range, the electroplating copper liquid can better contact with the electroplating copper liquid by virtue of the surface performance of the substrate membrane surface at this time, and the copper liquid can enter the hole by siphon effect to completely fill the hole, effectively avoiding the pore wall void phenomenon. When the pore size is less than 10nm, there will be a problem that the copper liquid will not enter the hole; when the pore size is greater than 50nm, there will be a problem that some or most of the holes cannot be completely filled. When the pore size is greater than 100nm, since most of the holes have less space that cannot be filled, the bonding performance of the copper layer and the substrate membrane surface deteriorates sharply.

[0016] As the composite powder filler, preferably, the volume-based cumulative 50% particle size of the porous silica is 0.3 to 2 μm.

[0017] If the particle size is too small, the particles are easy to agglomerate, and there will be large pores on the membrane surface of the molded product substrate. Plating copper on the membrane surface with large pores will increase the problem of pore wall voids. If the particle size is too large, the siphon effect cannot be formed, and the copper liquid is difficult to completely fill the empty holes, and the bonding performance between the copper layer of the finished PCB circuit board and the substrate membrane surface is poor.

[0018] As the preferred composite powder filler, based on the BET method, the specific surface area of ​​porous silica is 15~150m 2 / g.

[0019] If the specific surface area is too small, the viscosity will increase sharply, the particles will easily agglomerate, and the film surface of the molded product substrate will have large pores. Plating copper on the film surface with large pores will increase the problem of pore wall voids. If the specific surface area is too large, the affinity between the substrate film surface and the electroplating copper liquid is insufficient, which will lead to the problem of pore wall voids. At the same time, insufficient affinity will make it difficult to form a siphon effect, and the copper liquid will find it difficult to enter the pores of the silica and fill the holes. The peeling strength between the copper layer of the finished PCB circuit board and the substrate film surface is poor.

[0020] As the preferred composite powder filler, the dense silica is spherical silica. Based on the BET method, the specific surface area of ​​the dense silica is 1.5 to 15 m 2 / g.

[0021] The present invention uses dense silica as the main filler. The main filler of the present invention needs to have a specific surface area of ​​1.5 to 15 m 2 / g range. If the specific surface area of ​​the main filler is too small, the viscosity will increase sharply, the particles will easily agglomerate, and there will be large pores on the membrane surface of the molded product substrate. Plating copper on the membrane surface with large pores will increase the problem of pore wall voids. If the specific surface area of ​​the main filler is too large, it will affect the affinity between the substrate membrane surface and the electroplating copper solution. Insufficient affinity will lead to pore wall voids.

[0022] As the composite powder filler, preferably, the volume-based cumulative 50% particle size of dense silica is 0.3 to 2 μm.

[0023] If the particle size of the main filler is too small, the particles are easy to agglomerate, and there will be large pores on the membrane surface of the molded product substrate. Plating copper on the membrane surface with large pores will increase the problem of pore wall voids. If the particle size of the main filler is too large, the filling rate is low, and large pores will be formed between the particles. Plating copper on the membrane surface with large pores will cause pore wall voids.

[0024] In a second aspect, the present invention provides a method for preparing a composite powder filler, that is, porous silica and dense silica are mixed in a weight ratio of (0.5~30):(70~99.5) to obtain a composite powder.

[0025] In a third aspect, based on the above, the present invention provides the use of the above composite powder filler in the preparation of substrate materials.

[0026] In a fourth aspect, based on the above, the present invention provides an application of the above composite powder filler in an accumulated insulating film (ABF).

[0027] The surface of the substrate or the insulating film is treated with acid or alkali to increase the roughness of the film surface, thereby increasing the affinity between the copper layer obtained by copper deposition and the film surface, which is beneficial to the close bonding of the copper layer and the film surface.

[0028] According to the present invention, after the above-mentioned composite powder filler is subjected to particle size classification, it is used in the preparation of substrate materials or in the deposition of insulating films, which can effectively improve the filling performance of the filler. Therefore, generally, the above-mentioned composite powder filler of the present invention is obtained by removing coarse particles larger than 3, 5, 10, or 20 microns by dry or wet screening or inertial classification, which still belongs to the protection scope of the technical solution of the present invention.

[0029] In the field of fillers, in order to improve the processing performance of fillers or the bonding performance with resin substrates, the composite powder is usually surface treated, for example, the filler is surface treated with a silane coupling agent. In order to improve the processing performance of fillers or the bonding performance with resin substrates, the composite powder filler of the invention is subjected to the above-mentioned surface treatment and then applied to the preparation of substrate materials or the deposition of insulating films, which still falls within the scope of protection of the technical solution of the present invention.

[0030] Compared with the prior art, the present invention has the following technical effects: 1. The present invention uses dense silica as a main filler and adds 0.5% to 30% by weight of porous silica therein, thereby improving the affinity between the substrate material and the electroplating copper solution while ensuring the filling rate of the filler, facilitating the combination of the electroplating copper solution with the film surface, and avoiding the formation of pore wall voids. At the same time, the copper layer of the prepared PCB circuit board is tightly combined with the substrate film surface, and has the characteristic of high peeling strength.

[0031] 2. The present invention uses dense silica as the main filler, which can make the prepared substrate material have a better filling rate and good mechanical properties, and can be used in scenes with greater stress or pressure. DETAILED DESCRIPTION

[0032] The present invention will be further described below in conjunction with embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should belong to the scope of protection of the present invention.

[0033] The invention provides a composite powder filler, which consists of porous silicon dioxide and dense silicon dioxide, wherein the weight of the porous silicon dioxide accounts for 0.5% to 30% of the total weight of the filler.

[0034] The problem of pore wall voids occurs when copper is deposited on a PCB circuit board, mainly due to poor interface compatibility between the substrate surface and the copper electroplating solution. The present invention uses porous silica and dense silica in a suitable ratio as composite fillers to make a substrate, and copper deposition on this substrate can effectively avoid the pore wall void phenomenon, wherein the suitable ratio is that the weight of the porous silica accounts for 0.5% to 30% of the total weight of the filler.

[0035] Using dense silica as filler can make the prepared substrate material have a good filling rate, good mechanical properties, and can be used in scenes with high stress or pressure, but too much dense silica will cause the bonding ability between the substrate material and the copper foil layer to deteriorate sharply, thus easily leading to the problem of hole wall voids during copper deposition. The present invention uses dense silica as the main filler and adds porous silica at a weight ratio of 0.5% to 30%, which can improve the affinity between the substrate material and the electroplating copper solution while ensuring the filling rate of the filler, facilitate the combination of the electroplating copper solution with the membrane surface, avoid the formation of the hole wall void problem, and the copper layer of the prepared PCB circuit board is tightly combined with the substrate membrane surface.

[0036] The porous silica with a weight ratio of 0.5% to 30% can absorb the electroplating copper liquid into the pores of the silica due to its pores during the copper deposition process with the help of the physical siphon effect, so that the copper liquid can be guided to quickly fill the drilled holes of the substrate during copper deposition, thereby improving the bonding performance between the copper layer of the finished PCB circuit board and the membrane surface of the substrate. Due to the existence of the siphon effect, the formation of voids in the hole wall is avoided.

[0037] In the above method of the present invention, the dense silica can be understood as non-porous silica. Generally, dense silica is a silica material with a relatively high density and a relatively compact structure, and its surface is dense and has no pores or fewer pores. The dense silica can be prepared by chemical synthesis, deflagration, flame melting, etc.

[0038] In one embodiment, preferably, based on the BJH method, the average pore size of the porous silica is 5-100 nm.

[0039] When the average number of the pore size of porous silica is 5-100nm, the formation of pore wall voids can be effectively avoided. If the pore size of porous silica is too small, the electroplating copper solution cannot enter the pores, which will cause the copper layer of the product PCB circuit board to have poor bonding performance with the substrate film surface. The present invention has been found through multiple tests that if the pore size of porous silica is too large, the electroplating copper solution cannot completely fill the pores, and at this time, the bonding performance of the copper layer of the product PCB circuit board with the substrate film surface is poor.

[0040] In one embodiment, preferably, based on the BJH method, the average pore size of the porous silica is 10-50 nm.

[0041] When the average pore size of porous silica is 10~50nm, the formation of pore wall voids can be more effectively avoided. Within this pore size range, the electroplating copper liquid can better contact with the electroplating copper liquid by virtue of the surface performance of the substrate membrane surface at this time, and the copper liquid can enter the hole by siphon effect to completely fill the hole, effectively avoiding the pore wall void phenomenon. When the pore size is less than 10nm, there will be a problem that the copper liquid will not enter the hole; when the pore size is greater than 50nm, there will be a problem that some or most of the holes cannot be completely filled. When the pore size is greater than 100nm, since most of the holes have less space that cannot be filled, the bonding performance of the copper layer and the substrate membrane surface deteriorates sharply.

[0042] In one embodiment, preferably, the volume-based cumulative 50% particle size of the porous silica is 0.3-2 μm.

[0043] If the particle size is too small, the particles are easy to agglomerate, and there will be large pores on the membrane surface of the molded product substrate. Plating copper on the membrane surface with large pores will increase the problem of pore wall voids. If the particle size is too large, the siphon effect cannot be formed, and the copper liquid is difficult to completely fill the empty holes, and the bonding performance between the copper layer of the finished PCB circuit board and the substrate membrane surface is poor.

[0044] In one embodiment, as a preference, based on the BET method, the specific surface area of ​​the porous silica is 15 to 150 m 2 / g.

[0045] If the specific surface area is too small, the viscosity will increase sharply, the particles will easily agglomerate, and the film surface of the molded product substrate will have large pores. Plating copper on the film surface with large pores will increase the problem of pore wall voids. If the specific surface area is too large, the affinity between the substrate film surface and the electroplating copper liquid is insufficient, which will lead to the problem of pore wall voids. At the same time, insufficient affinity will make it difficult to form a siphon effect, and the copper liquid will find it difficult to enter the pores of the silica and fill the holes. The peeling strength between the copper layer of the finished PCB circuit board and the substrate film surface is poor.

[0046] In one embodiment, preferably, the dense silica is spherical silica, and based on the BET method, the specific surface area of ​​the dense silica is 1.5 to 15 m 2 / g.

[0047] The present invention uses dense silica as the main filler. The main filler of the present invention needs to have a specific surface area of ​​1.5 to 15 m 2 / g range. If the specific surface area of ​​the main filler is too small, the viscosity will increase sharply, the particles will easily agglomerate, and there will be large pores on the membrane surface of the molded product substrate. Plating copper on the membrane surface with large pores will increase the problem of pore wall voids. If the specific surface area of ​​the main filler is too large, it will affect the affinity between the substrate membrane surface and the electroplating copper solution. Insufficient affinity will lead to pore wall voids.

[0048] In one embodiment, preferably, the volume-based cumulative 50% particle size of the dense silica is 0.3-2 μm.

[0049] If the particle size of the main filler is too small, the particles are easy to agglomerate, and there will be large pores on the membrane surface of the molded product substrate. Plating copper on the membrane surface with large pores will increase the problem of pore wall voids. If the particle size of the main filler is too large, the filling rate is low, and large pores will be formed between the particles. Plating copper on the membrane surface with large pores will cause pore wall voids.

[0050] Based on the above filler, the present invention provides a method for preparing a composite powder filler, that is, porous silica and dense silica are mixed in a weight ratio of (0.5~30): (70~99.5) to obtain a composite powder.

[0051] Furthermore, based on the above, the present invention provides the use of the above composite powder filler in the preparation of substrate materials.

[0052] Furthermore, based on the above, the present invention provides the use of the above composite powder filler in a built-up insulating film (ABF).

[0053] The surface of the substrate or the insulating film is treated with acid or alkali to increase the roughness of the film surface, thereby increasing the affinity between the copper layer obtained by copper deposition and the film surface, which is beneficial to the close bonding of the copper layer and the film surface.

[0054] According to the present invention, after the above-mentioned composite powder filler is subjected to particle size classification, it is used in the preparation of substrate materials or in the deposition of insulating films, which can effectively improve the filling performance of the filler. Therefore, generally, the above-mentioned composite powder filler of the present invention is obtained by removing coarse particles larger than 3, 5, 10, or 20 microns by dry or wet screening or inertial classification, which still belongs to the protection scope of the technical solution of the present invention.

[0055] In the field of fillers, in order to improve the processing performance of fillers or the bonding performance with resin substrates, the composite powder is usually surface treated, for example, the filler is surface treated with a silane coupling agent. In order to improve the processing performance of fillers or the bonding performance with resin substrates, the composite powder filler of the invention is subjected to the above-mentioned surface treatment and then applied to the preparation of substrate materials or the deposition of insulating films, which still falls within the scope of protection of the technical solution of the present invention.

[0056] For ease of understanding, the present invention is further described below in conjunction with specific embodiments. In the following embodiments, Zhejiang Sanshiji New Materials Technology Co., Ltd. is abbreviated as Sanshiji Company.

[0057] Example 1 Preparation of composite filler The porous silica (purchased from Sanshiji Company, model number YYW0605) and the dense silica (purchased from Sanshiji Company, model number EQK0605) were evenly mixed to obtain a composite filler, in which the porous silica accounted for 5% and the dense silica accounted for 95% by weight.

[0058] in: Based on the BJH method, the average pore size of porous silica is 16 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of porous silica is 0.6 μm, and the true density is 2.33 g / cm 3 .

[0059] Based on the BJH method, the specific surface area of ​​dense silica is 5.5 m 2 / g; the volume-based cumulative 50% particle size (D50) of the dense silica was 0.6 μm.

[0060] Example 2 Preparation of composite filler The porous silica (purchased from Sanshiji Company, model number YYW0305) and the dense silica (purchased from Sanshiji Company, model number EQK0305) were evenly mixed to obtain a composite filler, in which the porous silica accounted for 0.5% by weight and the dense silica accounted for 99.5% by weight.

[0061] in: Based on the BJH method, the average pore size of porous silica is 5 nm and the specific surface area is 150 m 2 / g; the volume-based cumulative 50% particle size (D50) of porous silica is 0.3 μm, and the true density is 2.34 g / cm 3 .

[0062] Based on the BJH method, the specific surface area of ​​dense silica is 15 m 2 / g; the volume-based cumulative 50% particle size (D50) of the dense silica was 0.3 μm.

[0063] Example 3 Preparation of composite filler The porous silica (purchased from Sanshiji Company, model number YYW1010) and the dense silica (purchased from Sanshiji Company, model number EQ1010) were evenly mixed to obtain a composite filler, in which the porous silica accounted for 15% and the dense silica accounted for 85% by weight.

[0064] in: Based on the BJH method, the average pore size of porous silica is 50 nm and the specific surface area is 50 m 2 / g; the volume-based cumulative 50% particle size (D50) of porous silica is 1 μm, and the true density is 2.35 g / cm 3 .

[0065] Based on the BJH method, the specific surface area of ​​dense silica is 3.5 m 2 / g; the volume-based cumulative 50% particle size (D50) of the dense silica was 1 μm.

[0066] Example 4 Preparation of composite filler The porous silica (purchased from Sanshiji Company, model number YYW2010) and the dense silica (purchased from Sanshiji Company, model number EQ2010) were evenly mixed to obtain a composite filler, in which the porous silica accounted for 30% by weight and the dense silica accounted for 70% by weight.

[0067] in: Based on the BJH method, the average pore size of porous silica is 100 nm and the specific surface area is 15 m 2 / g; the volume-based cumulative 50% particle size (D50) of porous silica is 2 μm, and the true density is 2.35 g / cm 3 .

[0068] Based on the BJH method, the specific surface area of ​​dense silica is 1.5 m 2 / g; the volume-based cumulative 50% particle size (D50) of the dense silica was 2 μm.

[0069] Example 5 Preparation of composite filler The porous silica (purchased from Sanshiji Company, model number YYW0605) and the dense silica (purchased from Sanshiji Company, model number EQK0605) were evenly mixed to obtain a composite filler, in which the porous silica accounted for 10% by weight and the dense silica accounted for 90% by weight.

[0070] in: Based on the BJH method, the average pore size of porous silica is 16 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of porous silica is 0.6 μm, and the true density is 2.33 g / cm 3 .

[0071] Based on the BJH method, the specific surface area of ​​dense silica is 5.5 m 2 / g; the volume-based cumulative 50% particle size (D50) of the dense silica was 0.6 μm.

[0072] Example 6 Preparation of composite filler The porous silica (purchased from Sanshiji Company, model number YYW0605) and the dense silica (purchased from Sanshiji Company, model number EQK0605) were evenly mixed to obtain a composite filler, in which the porous silica accounted for 20% by weight and the dense silica accounted for 80% by weight.

[0073] in: Based on the BJH method, the average pore size of porous silica is 16 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of porous silica is 0.6 μm, and the true density is 2.33 g / cm 3 .

[0074] Based on the BJH method, the specific surface area of ​​dense silica is 5.5 m 2 / g; the volume-based cumulative 50% particle size (D50) of the dense silica was 0.6 μm.

[0075] Example 7 Preparation of composite filler The difference between this embodiment and embodiment 1 is that the average pore size of the porous silica is 6 nm. The preparation method is as follows: The porous silica (purchased from Sanshiji Company, model number YYW06B5) and the dense silica (purchased from Sanshiji Company, model number EQK0605) were evenly mixed to obtain a composite filler, in which the porous silica accounted for 5% and the dense silica accounted for 95% by weight.

[0076] in: Based on the BJH method, the average pore size of porous silica is 6 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of porous silica is 0.6 μm, and the true density is 2.30 g / cm 3 .

[0077] Based on the BJH method, the specific surface area of ​​dense silica is 5.5 m 2 / g; the volume-based cumulative 50% particle size (D50) of the dense silica was 0.6 μm.

[0078] Example 8 Preparation of composite filler The difference between this embodiment and embodiment 1 is that the average pore size of the porous silica is 8 nm. The preparation method is as follows: The porous silica (purchased from Sanshiji Company, model number YYW06C5) and the dense silica (purchased from Sanshiji Company, model number EQK0605) were evenly mixed to obtain a composite filler, in which the porous silica accounted for 5% and the dense silica accounted for 95% by weight.

[0079] in: Based on the BJH method, the average pore size of porous silica is 8 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of porous silica is 0.6 μm, and the true density is 2.31 g / cm 3 .

[0080] Based on the BJH method, the specific surface area of ​​dense silica is 5.5 m 2 / g; the volume-based cumulative 50% particle size (D50) of the dense silica was 0.6 μm.

[0081] Example 9 Preparation of composite filler The difference between this embodiment and embodiment 1 is that the average pore size of the porous silica is 10 nm. The preparation method is as follows: The porous silica (purchased from Sanshiji Company, model number YYW06D5) and the dense silica (purchased from Sanshiji Company, model number EQK0605) were evenly mixed to obtain a composite filler, in which the porous silica accounted for 5% and the dense silica accounted for 95% by weight.

[0082] in: Based on the BJH method, the average pore size of porous silica is 10 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of porous silica is 0.6 μm, and the true density is 2.31 g / cm 3 .

[0083] Based on the BJH method, the specific surface area of ​​dense silica is 5.5 m 2 / g; the volume-based cumulative 50% particle size (D50) of the dense silica was 0.6 μm.

[0084] Example 10 Preparation of composite filler The difference between this embodiment and embodiment 1 is that the average pore size of the porous silica is 20 nm. The preparation method is as follows: The porous silica (purchased from Sanshiji Company, model number YYW06E5) and the dense silica (purchased from Sanshiji Company, model number EQK0605) were evenly mixed to obtain a composite filler, in which the porous silica accounted for 5% and the dense silica accounted for 95% by weight.

[0085] in: Based on the BJH method, the average pore size of porous silica is 20 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of porous silica is 0.6 μm, and the true density is 2.32 g / cm 3 .

[0086] Based on the BJH method, the specific surface area of ​​dense silica is 5.5 m 2 / g; the volume-based cumulative 50% particle size (D50) of the dense silica was 0.6 μm.

[0087] Example 11 Preparation of composite filler The difference between this embodiment and embodiment 1 is that the average pore size of the porous silica is 34 nm. The preparation method is as follows: The porous silica (purchased from Sanshiji Company, model number YYW06F5) and the dense silica (purchased from Sanshiji Company, model number EQK0605) were evenly mixed to obtain a composite filler, in which the porous silica accounted for 5% and the dense silica accounted for 95% by weight.

[0088] in: Based on the BJH method, the average pore size of porous silica is 34 nm and the specific surface area is 75 m 2 / g; the volume-based cumulative 50% particle size (D50) of porous silica is 0.6 μm, and the true density is 2.34 g / cm 3 .

[0089] Based on the BJH method, the specific surface area of ​​dense silica is 5.5 m 2 / g; the volume-based cumulative 50% particle size (D50) of the dense silica was 0.6 μm.

[0090] Example 12 Preparation of composite filler The difference between this embodiment and embodiment 1 is that the average pore size of the porous silica is 50 nm. The preparation method is as follows: The porous silica (purchased from Sanshiji Company, model number YYW06G5) and the dense silica (purchased from Sanshiji Company, model number EQK0605) were evenly mixed to obtain a composite filler, in which the porous silica accounted for 5% and the dense silica accounted for 95% by weight.

[0091] in: Based on the BJH method, the average pore size of porous silica is 50 nm and the specific surface area is 75 m 2 / g; the volume-based cumulative 50% particle size (D50) of porous silica is 0.6 μm, and the true density is 2.32 g / cm 3 .

[0092] Based on the BJH method, the specific surface area of ​​dense silica is 5.5 m 2 / g; the volume-based cumulative 50% particle size (D50) of the dense silica was 0.6 μm.

[0093] Example 13 Preparation of composite filler The difference between this embodiment and embodiment 1 is that the average pore size of the porous silica is 67 nm. The preparation method is as follows: The porous silica (purchased from Sanshiji Company, model number YYW06H5) and the dense silica (purchased from Sanshiji Company, model number EQK0605) were evenly mixed to obtain a composite filler, in which the porous silica accounted for 5% and the dense silica accounted for 95% by weight.

[0094] in: Based on the BJH method, the average pore size of porous silica is 67 nm and the specific surface area is 74 m 2 / g; the volume-based cumulative 50% particle size (D50) of porous silica is 0.6 μm, and the true density is 2.32 g / cm 3 .

[0095] Based on the BJH method, the specific surface area of ​​dense silica is 5.5 m 2 / g; the volume-based cumulative 50% particle size (D50) of the dense silica was 0.6 μm.

[0096] Example 14 Preparation of composite filler The difference between this embodiment and embodiment 1 is that the average pore size of the porous silica is 82 nm. The preparation method is as follows: The porous silica (purchased from Sanshiji Company, model number YYW06J5) and the dense silica (purchased from Sanshiji Company, model number EQK0605) were evenly mixed to obtain a composite filler, in which the porous silica accounted for 5% and the dense silica accounted for 95% by weight.

[0097] in: Based on the BJH method, the average pore size of porous silica is 82 nm and the specific surface area is 76 m 2 / g; the volume-based cumulative 50% particle size (D50) of porous silica is 0.6 μm, and the true density is 2.36 g / cm 3 .

[0098] Based on the BJH method, the specific surface area of ​​dense silica is 5.5 m 2 / g; the volume-based cumulative 50% particle size (D50) of the dense silica was 0.6 μm.

[0099] Example 15 Preparation of composite filler The difference between this embodiment and embodiment 1 is that the average pore size of the porous silica is 2 nm. The preparation method is as follows: The porous silica (purchased from Sanshiji Company, model number YYW06A5) and the dense silica (purchased from Sanshiji Company, model number EQK0605) were evenly mixed to obtain a composite filler, in which the porous silica accounted for 5% and the dense silica accounted for 95% by weight.

[0100] in: Based on the BJH method, the average pore size of porous silica is 2 nm and the specific surface area is 72 m 2 / g; the volume-based cumulative 50% particle size (D50) of porous silica is 0.6 μm, and the true density is 2.10 g / cm 3 .

[0101] Based on the BJH method, the specific surface area of ​​dense silica is 5.5 m 2 / g; the volume-based cumulative 50% particle size (D50) of the dense silica was 0.6 μm.

[0102] Example 16 Preparation of composite filler The difference between this embodiment and embodiment 1 is that the average pore size of the porous silica is 120 nm. The preparation method is as follows: The porous silica (purchased from Sanshiji Company, model number YYW06K5) and the dense silica (purchased from Sanshiji Company, model number EQK0605) were evenly mixed to obtain a composite filler, in which the porous silica accounted for 5% and the dense silica accounted for 95% by weight.

[0103] in: Based on the BJH method, the average pore size of porous silica is 120 nm and the specific surface area is 91 m 2 / g; the volume-based cumulative 50% particle size (D50) of porous silica is 0.6 μm, and the true density is 2.35 g / cm 3 .

[0104] Based on the BJH method, the specific surface area of ​​dense silica is 5.5 m 2 / g; the volume-based cumulative 50% particle size (D50) of the dense silica was 0.6 μm.

[0105] Example 17 Preparation of composite filler The difference between this embodiment and embodiment 1 is that the volume-based cumulative 50% particle size (D50) of the porous silica is 0.2 μm. The preparation method is as follows: Porous silica (purchased from Sanshiji Company, model number YYW0202) and dense silica (purchased from Sanshiji Company, model number EQK0605) were evenly mixed to obtain a composite filler, in which the porous silica accounted for 5% and the dense silica accounted for 95% by weight.

[0106] in: Based on the BJH method, the average pore size of porous silica is 16 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of porous silica is 0.2 μm, and the true density is 2.33 g / cm 3 .

[0107] Based on the BJH method, the specific surface area of ​​dense silica is 5.5 m 2 / g; the volume-based cumulative 50% particle size (D50) of the dense silica was 0.6 μm.

[0108] Example 18 Preparation of composite filler The difference between this embodiment and embodiment 1 is that the volume-based cumulative 50% particle size (D50) of the porous silica is 3 μm. The preparation method is as follows: The porous silica (purchased from Sanshiji Company, model number YYW3010) and the dense silica (purchased from Sanshiji Company, model number EQK0605) were evenly mixed to obtain a composite filler, in which the porous silica accounted for 30% by weight and the dense silica accounted for 70% by weight.

[0109] in: Based on the BJH method, the average pore size of porous silica is 16 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of porous silica is 3 μm, and the true density is 2.34 g / cm 3 .

[0110] Based on the BJH method, the specific surface area of ​​dense silica is 5.5 m 2 / g; the volume-based cumulative 50% particle size (D50) of the dense silica was 0.6 μm.

[0111] Example 19 Preparation of composite filler The difference between this embodiment and embodiment 1 is that the specific surface area of ​​dense silica is 16.8 m 2 / g; the volume-based cumulative 50% particle size (D50) of dense silica is 0.2μm. The preparation method is as follows: The porous silica (purchased from Sanshiji Company, model number YYW0605) and the dense silica (purchased from Sanshiji Company, model number EQK0205) were evenly mixed to obtain a composite filler, in which the porous silica accounted for 5% and the dense silica accounted for 95% by weight.

[0112] in: Based on the BJH method, the average pore size of porous silica is 16 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of porous silica is 0.6 μm, and the true density is 2.33 g / cm 3 .

[0113] Based on the BJH method, the specific surface area of ​​dense silica is 16.8 m 2 / g; the volume-based cumulative 50% particle size (D50) of the dense silica was 0.2 μm.

[0114] Example 20 Preparation of composite filler The difference between this embodiment and embodiment 1 is that the specific surface area of ​​dense silica is 1.3 m 2 / g; the volume-based cumulative 50% particle size (D50) of dense silica is 0.2μm. The preparation method is as follows: The porous silica (purchased from Sanshiji Company, model number YYW0605) and the dense silica (purchased from Sanshiji Company, model number EQ2410) were evenly mixed to obtain a composite filler, in which the porous silica accounted for 5% and the dense silica accounted for 95% by weight.

[0115] in: Based on the BJH method, the average pore size of porous silica is 16 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of porous silica is 0.6 μm, and the true density is 2.33 g / cm 3 .

[0116] Based on the BJH method, the specific surface area of ​​dense silica is 1.3 m 2 / g; the volume-based cumulative 50% particle size (D50) of the dense silica was 2.4 μm.

[0117] Example 21 Preparation of a built-up printed circuit board Take 20 parts by weight of bisphenol A epoxy resin (828EL), 10 parts by weight of naphthalene epoxy resin (ESN-475V), 10 parts by weight of naphthalene epoxy resin (HP-6000), 60 parts by weight of composite filler, 20 parts by weight of active ester (HPC-8000-65T), 3 parts by weight of phenoxy resin (YX7553BH30), 0.2 parts by weight of 4-dimethylaminopyridine (DMAP), 10 parts by weight of modified maleimide and 300 parts by weight of cyclohexanone, mix them evenly at 1000 rpm for 1 hour, then coat them on PET release film, dry them, bake them in a 120°C oven for 5 minutes, and obtain a semi-cured resin film (i.e., a layer-building adhesive film) coated on the PET release film, wherein the thickness of the resin film is 40 μm. Take 3 resin films, tear off the PET release film, and then stack them together to test the viscosity of the resin film. The results are shown in Table 1. The semi-cured resin film is laminated and pressed with the browned PCB board (as the core board, the inner board in the multi-layer PCB board) to obtain the substrate material, wherein the pressing temperature is 100°C, the pressure is 0.5MPa, and the time is 1min. Then, the substrate material is laser drilled with a hole diameter of 70μm, and after the release film is torn off, the resin film is soaked in concentrated sulfuric acid for desmearing surface treatment (Desmear treatment) to obtain a rough surface with holes in the resin film, and then copper electroplating (copper electroplating liquid model MVTP1, purchased from ATOTECH, Germany) is performed on the rough resin film surface to form a laminated printed circuit board with circuits.

[0118] Among them, the surface treatment method is: soaking in a glycol ether sodium hydroxide aqueous solution (model MV Sweller, purchased from ATOTECH, Germany) at 70°C for 10 minutes, then washing with deionized water for 2 minutes, then soaking in a potassium permanganate solution (model MV P Etch, purchased from ATOTECH, Germany) at 80°C for 30 minutes, then washing with deionized water for 2 minutes, and then soaking in an acidic aqueous solution (model MV Reduction Cleaner, purchased from ATOTECH, Germany) at 50°C for 5 minutes to obtain a substrate with a surface roughened resin film.

[0119] The electroplated copper layer has a thickness of 25 μm.

[0120] Comparative Example 1 The difference between this comparative example and Example 1 is that the weight of porous silica accounts for 0.2% of the total weight of the filler. The preparation method is as follows: The porous silica (purchased from Sanshiji Company, model number YYW0605) and the dense silica (purchased from Sanshiji Company, model number EQK0605) were evenly mixed to obtain a composite filler, in which the porous silica accounted for 0.2% by weight and the dense silica accounted for 99.8% by weight.

[0121] in: Based on the BJH method, the average pore size of porous silica is 16 nm and the specific surface area is 80 m 2 / g; the volume-based cumulative 50% particle size (D50) of porous silica is 0.6 μm, and the true density is 2.33 g / cm 3 .

[0122] Based on the BJH method, the specific surface area of ​​dense silica is 5.5 m 2 / g; the volume-based cumulative 50% particle size (D50) of the dense silica was 0.6 μm.

[0123] Comparative Example 2 The difference between this comparative example and Example 1 is that the weight of porous silica accounts for 34% of the total weight of the filler. The preparation method is as follows: The porous silica (purchased from Sanshiji Company, model number YYW0605) and the dense silica (purchased from Sanshiji Company, model number EQK0605) were evenly mixed to obtain a composite filler, in which the porous silica accounted for 34% and the dense silica accounted for 66% by weight.

[0124] in: Based on the BJH method, the average pore size of porous silica is 16 nm and the specific surface area is 80 m2 / g; the volume-based cumulative 50% particle size (D50) of porous silica is 0.6 μm, and the true density is 2.33 g / cm 3 .

[0125] Based on the BJH method, the specific surface area of ​​dense silica is 5.5 m 2 / g; the volume-based cumulative 50% particle size (D50) of the dense silica was 0.6 μm.

[0126] Performance Characterization The composite fillers obtained in Examples 1 to 20 and Comparative Examples 1 to 2 were used to prepare laminated printed circuit boards in the manner of Example 21. The number of voids in the field of view was detected using a SEM electron microscope at a magnification of 20,000 times, and the copper foil peeling strength and dielectric loss Df of the circuit board were tested. The results are shown in Tables 1 and 2. The copper foil peeling strength was tested using the IPC-TM-6502.4.9 method; the dielectric loss Df was tested using the SPDR (splite post dielectric resonator) method, and the dielectric loss of the substrate was tested in accordance with the IPC4101 standard. The test conditions were A state, 10 GHz, and the test instrument was a high-frequency vector network analyzer.

[0127] Table 1 Table 2 From the characterization data in Table 1 and Table 2, we can see that: (1) The present invention uses dense silica as the main filler and adds porous silica at a weight ratio of 0.5% to 30%. Under the premise of ensuring the filling rate of the filler, the affinity between the substrate material and the electroplating copper solution can be improved, the electroplating copper solution is easy to combine with the membrane surface, and the formation of pore wall voids is effectively reduced. The copper layer of the prepared PCB circuit board is tightly combined with the substrate membrane surface. Based on the composite filler of the present invention, at a magnification of 20,000 times, the number of voids in the field of view can be reduced to less than 10, and can be as low as 0.

[0128] Further, based on the characterization data of the present invention, as the preferred composite filler of the present invention, the average pore size of porous silica is 5-100 nm; further preferably, the average pore size of porous silica is 10-50 nm. Specifically, the average pore size of porous silica in Examples 7 to 16 is 6 nm, 8 nm, 10 nm, 20 nm, 34 nm, 50 nm, 67 nm, 82 nm, 2 nm, and 120 nm, respectively, that is, when the average pore size of porous silica is compared by a single variable, when the average pore size of porous silica is 10 nm, 20 nm, 34 nm, and 50 nm, respectively, the number of voids in the product substrate can be reduced to 0, and when the pore size is not within the range of 10-50 nm, the number of voids increases to varying degrees. The reason is that within the pore size range of 10-50nm, the electroplating copper liquid can make good contact with the electroplating copper liquid by virtue of the surface performance of the substrate film surface at this time, and the copper liquid can enter the hole by siphon effect to completely fill the hole, effectively avoiding the hole wall void phenomenon. When the pore size is less than 10nm, there will be a problem that the copper liquid will not enter the hole; when the pore size is greater than 50nm, there will be a problem that some or most of the holes cannot be completely filled. When the pore size is greater than 100nm, since most of the holes have less space that cannot be filled, the bonding performance between the copper layer and the substrate film surface deteriorates sharply.

[0129] Furthermore, based on the characterization data of the present invention, as a preferred composite filler of the present invention, the specific surface area of ​​dense silica is 1.5 to 15 m 2 / g, and its volume-based cumulative 50% particle size is 0.3-2 μm. Specifically, the volume-based cumulative 50% particle size of the dense silica of Example 1, Example 19-Example 20 is 0.6 μm, 0.2 μm, and 2.4 μm, respectively, and the specific surface area of ​​the dense silica is 5.5 m 2 / g, 16.8 m 2 / g, 1.3 m 2 / g, the number of voids in the substrates of the products of Example 19 and Example 20 increased to varying degrees, increasing to 4 and 5 respectively. Combining with other examples, it can be seen that the specific surface area of ​​dense silica is 1.5~15m 2 / g, and when the cumulative 50% particle size based on volume is 0.3~2μm, the number of voids is small. The reason is that when the particle size of dense silica as the main filler is less than 0.3μm, or the specific surface area is greater than 15m 2 / g, the particles are easy to agglomerate, and there will be large pores on the membrane surface of the molded product substrate. Plating copper on the membrane surface with large pores will increase the problem of pore wall voids; when the particle size is greater than 2μm, or the specific surface area is less than 1.5m 2 / g, it will lead to poor surface bonding performance, low filling rate, and larger pores between the particles. Copper deposition on the membrane surface with larger pores will lead to the problem of voids in the pore walls.

[0130] Furthermore, based on the characterization data of the present invention, as the preferred composite filler of the present invention, the volume-based cumulative 50% particle size of porous silica is 0.3~2μm. Specifically, the volume-based cumulative 50% particle size of porous silica in Example 1, Example 17~Example 18 is 0.6μm, 0.2μm, and 3.0μm, respectively, that is, when the D50 particle size of porous silica is compared by a single variable, when D50 is 0.2μm and 3.0μm, respectively, the number of voids in the product substrate increases to varying degrees, increasing to 6 and 10, respectively. In combination with other embodiments, it can be seen that when the volume-based cumulative 50% particle size of porous silica is within the range of 0.3~2μm, the number of voids is small. The reason is that when the D50 particle size is less than 0.3μm, the particles are easy to agglomerate, and there will be large pores on the membrane surface of the molded product substrate. Copper deposition on the membrane surface with large pores will increase the problem of pore wall voids. When the D50 particle size is greater than 2μm, the siphon effect cannot be formed, and the copper liquid is difficult to completely fill the hole. The bonding performance between the copper layer of the finished PCB circuit board and the substrate membrane surface is poor, which will also increase the problem of pore wall voids.

[0131] (2) From the comparative analysis of Example 1 and Comparative Examples 1 and 2, it can be seen that the porous silica in Comparative Examples 1 and 2 accounts for 0.2% and 34% of the total weight of the composite filler, respectively. The number of voids in the field of view of Comparative Examples 1 and 2 increases sharply, to 12 and 15, respectively. It can be seen that in order to effectively reduce the formation of pore wall voids, it is necessary to control the weight ratio of the porous silica added therein to be within the range of 0.5% to 30% of the total weight when dense silica is used as the main filler. At the same time, the dielectric loss Df of Comparative Examples 1 and 2 increases, and the peel strength of Comparative Example 1 decreases.

[0132] In the embodiment of the present invention, the true density is measured by a true density meter using a dry pycnometer based on nitrogen.

[0133] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0134] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A composite powder filler, characterized in that: The filler is composed of porous silica and dense silica, wherein the weight of the porous silica accounts for 0.5% to 30% of the total weight of the filler.

2. A composite powder filler according to claim 1, characterized in that: Based on the BJH method, the average pore size of porous silica is 5 to 100 nm.

3. A composite powder filler according to claim 2, characterized in that: Based on the BJH method, the average pore size of porous silica is 10 to 50 nm.

4. A composite powder filler according to claim 1, characterized in that: The volume-based cumulative 50% particle size of the porous silica is 0.3 to 2 μm.

5. A composite powder filler as claimed in claim 1, 2 or 4, characterized in that: Based on the BET method, the specific surface area of ​​porous silica is 15~150m 2 / g.

6. A composite powder filler according to claim 1, characterized in that: The dense silica is spherical silica. Based on the BET method, the specific surface area of ​​the dense silica is 1.5 to 15 m 2 / g.

7. A composite powder filler according to claim 1 or 6, characterized in that: The volume-based cumulative 50% particle size of dense silica is 0.3 to 2 μm.

8. A method for preparing a composite powder filler, characterized in that: The porous silica and the dense silica are mixed in a weight ratio of (0.5~30):(70~99.5).

9. Use of the filler according to any one of claims 1 to 7, or the filler prepared by the preparation method according to claim 8 in preparing a substrate material or in depositing an insulating film.

10. The use according to claim 9, characterized in that: The substrate or the film surface is treated with acid or alkali.

11. The use according to claim 9, characterized in that: The filler is subjected to dry or wet sieving or inertial classification to remove coarse particles larger than 3, 5, 10, or 20 μm.

12. The use according to claim 9, characterized in that: The filler is surface treated.

Citation Information

Patent Citations

  • Application of circuit board hole-filling electroplating leveling agent

    CN113430597A